Digital terrain analysis in soil science and geology - Florinsky, Igor V. (Academic Press, 2011)
Digital Terrain Analysis in Soil Science and Geology provides soil scientists and geologists with an integrated view of the principles and methods of digital terrain analysis. Its attention to first principles and focus on error analysis makes it a useful resource for scientists to uncover the method applications particular to their needs. Digital Terrain Analysis in Soil Science and Geology covers a wide range of applications in the context of multi-scale problems of soil science and geology. Presents a mathematical approach from a single author who is actively researching in the field and has published a number of fundamental papers. Outlines principles, methods, then follows with examples in a simple set-up that builds on content. Provides an integrated view of the principles and methods of digital terrain analysis.